Prevalence of pneumonia associated with measles among hospitalized children in Maiwand Teaching Hospital, Kabul, Afghanistan - Pour, Zaker Hussain Hussain; Masoomi, Ainulllah; Barakzai, Yama; Karimi, Qurban Ali; Ahmadi, Abdul Qudoos (Eximia, 2023)
Objective: The aim of this study is to determine the prevalence of measles and pneumonia associated with measles among children who were admitted to the pediatric department of Maiwand Teaching Hospital, Kabul, Afghanistan. Study Design: Descriptive, Cross-sectional. Place and Duration: Pediatrics department of Maiwand Teaching Hospital, Kabul, Afghanistan, for six months (April 2022 to October 2022). Methods: A total of 557 patients, including children and infants of both genders, were included in this study. Patients’ diagnosed measles and the frequency of pneumonia among all patients were assessed. The SPSS 22.0 version was used to analyze all of the data. Results: The average rate of measles was found to be 22.8% among hospitalized children. There were 289 (51.9%) male patients and 268 (48. 1%) female patients. In terms of age, 17 (3.1%) of the patients were under six months old, 150 (26.7%) were 6-12 months old, 310 (55.7%) were 13-60 months old, 68 (12.2%) were 61-120 months old, and 12 (2.2%) were more than 120 months old. The prevalence of pneumonia was found among 121 (21.7%) cases. 112 (20.1%) cases had received the measles vaccination. Conclusion: This study found that the prevalence of pneumonia among children with measles was 21.7%, which is relatively high. It was due to a lack of vaccinations. It can be controlled by providing awareness about vaccination to the parents of children.